Analisis Bentuk Akhlak Kepada Teman dan Tetangga Berdasarkan Al-Qur’an - Puja Hayati; Hafifa Hafifa; Fajri Massaid; Elvita Sarah Azzahra; Wismanto Wismanto (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Morals in the Islamic religion are morals that truly maintain human existence as honorable creatures in accordance with their nature. The existence of morals in a human being to create actions or behavior that are in accordance with the guidance of the Al-Qur'an and the Hadith of the Prophet Muhammad. However, in the current reality, bad moral decadence always adorns the attitudes and behavior of humans today. Even worse, this fact cannot be denied that bad morals are sometimes born and emerge from among Muslims who should be well maintained, reduced manners. , has no manners even towards friends and neighbors. As time goes by, the quality of the existence of noble morals decreases, and if left unchecked, these noble morals will continue to decline and even disappear. Therefore, this research aims to determine the form of good morals towards friends and neighbors. In this writing, the research method used is a literature study-based research method by collecting documents from various journals. The results of this research show that morals towards friends and neighbors in the Qur'an include helping, giving something, visiting sick people, being happy about neighbors' success and giving each other advice. And the point is to do good to friends and neighbors.